2020
DOI: 10.2139/ssrn.3579251
|View full text |Cite
|
Sign up to set email alerts
|

Labour Supply in the Early Stages of the COVID-19 Pandemic: Empirical Evidence on Hours, Home Office, and Expectations

Abstract: Using a survey module administered in late March 2020, we analyze how working hours change under the social distancing regulations enacted to fight the CoViD-19 pandemic. We study the Netherlands, which are a prototypical Western European country, both in terms of its welfare system and its response to the pandemic. We show that total hours decline and more so for the self-employed and those with lower educational degrees. The education gradient appears because workers with a tertiary degree work a much higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 4 publications
(5 reference statements)
2
23
0
1
Order By: Relevance
“…Second, this is one of the first studies to investigate whether the COVID‐19 pandemic has changed gender‐specific patterns of the use of remote work. By examining not only gender‐specific use of remote work but also the hours worked from home and the reasons for not working from home, the findings of our study extend the insights from previous research that investigated the share of jobs that can be performed from home (Arntz et al., 2020 ; Brynjolfsson et al., 2020 ; von Gaudecker et al., 2020 ; Moehring, Reifenscheid, & Weiland, 2021 ), the increase in the use of remote work during the pandemic (Alipour et al., 2021 ; Brynjolfsson et al., 2020 ; von Gaudecker et al., 2020 ), and its consequences for the gendered division of labor (Zoch et al., 2021 ). By examining both changes in the use and reasons for the non‐use of remote work, our study assesses (a) differences in the use of this arrangement before and during the pandemic among mothers, fathers, childless men, and childless women; and (b) whether these differences align with changes in perceived cultural barriers to and changing desires for remote work.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Second, this is one of the first studies to investigate whether the COVID‐19 pandemic has changed gender‐specific patterns of the use of remote work. By examining not only gender‐specific use of remote work but also the hours worked from home and the reasons for not working from home, the findings of our study extend the insights from previous research that investigated the share of jobs that can be performed from home (Arntz et al., 2020 ; Brynjolfsson et al., 2020 ; von Gaudecker et al., 2020 ; Moehring, Reifenscheid, & Weiland, 2021 ), the increase in the use of remote work during the pandemic (Alipour et al., 2021 ; Brynjolfsson et al., 2020 ; von Gaudecker et al., 2020 ), and its consequences for the gendered division of labor (Zoch et al., 2021 ). By examining both changes in the use and reasons for the non‐use of remote work, our study assesses (a) differences in the use of this arrangement before and during the pandemic among mothers, fathers, childless men, and childless women; and (b) whether these differences align with changes in perceived cultural barriers to and changing desires for remote work.…”
Section: Introductionsupporting
confidence: 77%
“…The COVID‐19 pandemic has led to a large increase in remote working to avoid infection risks at work sites and during commutes (Arntz et al., 2020 ; Brynjolfsson et al., 2020 ; von Gaudecker et al., 2020 ). As organizations suddenly had to give large proportions of their employees in different ranks and jobs the possibility of working from home, this may have altered the views of both employers and employees on the advantages and disadvantages of remote working.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is estimated that the contemporary German labor market offers the potential for almost 40% of all workers to work from home, prior to the pandemic only 12% did so, at least partially [ 5 ]. The current pandemic has witnessed a dramatic increase in working from home [ 4 , 26 , 27 ]. As a precaution to prevent the further spread of the virus by reducing social contacts, the government imposed lockdowns—including the closure of non-essential businesses—and urged employers and employees to perform work from home where feasible.…”
Section: Introductionmentioning
confidence: 99%
“…In the construction industry, for example, site-based employees work longer, more irregular hours than office-based employees (Lingard and Francis 2004). Thus, in the context of the present study, change in work location due to the pandemic (i.e., WFH and working partly in normal workplace and partly from home) is greatly associated with the respondents' hours worked (von Gaudecker et al 2020). Indeed, Lingard and Francis (2004) found that construction employees' work-life experiences appear to be more closely related to the nature of employees' job conditions, as indicated by work location and number of working hours.…”
Section: Discussionmentioning
confidence: 59%